Prediction of Maximum Pit Sizes in Elevated Chloride Concentrations and Temperatures. Issue 11 (7th June 2019) - Katona, R. M.; Carpenter, J.; Schindelholz, E. J.; Kelly, R. G.
Abstract : Calculated maximum pit sizes for stainless steel 304L (SS304L) are presented for atmospheric conditions with elevated chloride concentrations and temperatures. These calculations were carried out by experimentally determining the pit stability product (( i · x ) sf ), repassivation potential ( Erp ), and cathodic kinetics. These results were aided by determination of a solubility curve as a function of temperature for a stoichiometric metal salt mixture of iron chloride (FeCl2 ), chromium chloride (CrCl3 ), and nickel chloride (NiCl2 ). Based on these newly measured saturation concentrations, metal ion diffusivities were calculated. Overall, it was found that ( i · x ) sf decreases with increasing chloride concentration and increases with increasing temperature. Erp was determined to decrease with increasing concentration and increase with increasing temperature. When incorporated into the maximum pit size model, these experimental results yielded a small increase in maximum pit size with increasing bulk chloride concentrations and/or increasing temperature.